2022
DOI: 10.1186/s13002-022-00518-8
|View full text |Cite
|
Sign up to set email alerts
|

An ethnobotany survey of wild plants used by the Tibetan people of the Yadong River Valley, Tibet, China

Abstract: Introduction Plant resources gathered from the wild are important sources of livelihood needs, especially for low-income populations living in remote areas, who rely on these plants for food, fuelwood, medicine and building materials. Yadong County is a valley at the border between the China, India and Bhutan in southern Tibet. Yadong is rich in biodiversity and culture, but ethnobotanical knowledge has not been systematically studied. This study aimed to document the ethnobotanical knowledge o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…We compared our study with other comprehensive ethnobotanical studies of the Tibetan people that have been performed in the Himalayan region. We mainly compared the differences in wild useful plant species among Gyirong (with a total of 110 species), Burang (with a total of 75 species) [27], and Yadong (with a total of 121 species) [22]. The results showed that 36 species of plants in the catalog of Gyirong and Yadong were the same, but only 17 species were the same in Gyirong and Burang.…”
Section: Comparison Of Wild Useful Plants Between Tibetan Ethnic Grou...mentioning
confidence: 99%
See 3 more Smart Citations
“…We compared our study with other comprehensive ethnobotanical studies of the Tibetan people that have been performed in the Himalayan region. We mainly compared the differences in wild useful plant species among Gyirong (with a total of 110 species), Burang (with a total of 75 species) [27], and Yadong (with a total of 121 species) [22]. The results showed that 36 species of plants in the catalog of Gyirong and Yadong were the same, but only 17 species were the same in Gyirong and Burang.…”
Section: Comparison Of Wild Useful Plants Between Tibetan Ethnic Grou...mentioning
confidence: 99%
“…This plant is widely distributed in the Himalayas of China and northern India and Nepal [57]. It is also used as an edible plant in many areas, for example, in Yadong County, Tibet, it has the same usage as Gyirong [22]. In Litang, Sichuan, China, the Tibetans also use the fresh bulb of the plant as a wild vegetable and spice [32].…”
Section: Important Wild Useful Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tibetans are one of the 56 ethnic minorities in China, mainly living in the Qinghai–Tibet Plateau, with an average altitude of over 4000 m [ 20 , 21 ]. They have extensive knowledge of wild useful plants [ 22 26 ]. As one of the nations living in the Qinghai–Tibet Plateau for generations, Tibetans can adapt to the harsh climate on the plateau, which is inseparable from the use of wild plants, while it is still relatively lacking research.…”
Section: Introductionmentioning
confidence: 99%